Global research on type 1 diabetes: A bibliometric study during 2001-2022 - Vaishya, Raju; Gupta, Brij Mohan; Singh, Yogendra; Bansal, Madhu; Vaish, Abhishek (Iberoamerican Journal of Science Measurement and Communication, 2024)
Objective. Type 1 diabetes (T1D) publications have increased over the past three decades. However, there is no study to address and identify gaps in this area and to plan future research. This study aims to analyze the global scientific production of T1D in terms of overall structure and hotspots. Methodology. The research literature on T1D from 2001 to 2022 was obtained and examined from the Scopus database. We then performed bibliometric analysis and network visualization using MS Excel and VOSviewer software. Results and Discussion. The global T1D research comprised 20473 publications, which witnessed 6.19% and 58.91% annual average and 10-year cumulative growth during 2001-2022. These together received 596950 citations, with an average Citation Per Paper (CPP) of 29.16. Of the total global publications, 6030 (29.45%) received external funding support from international agencies and 19553 citations (with an average CPP of 32.43). The global publications were sourced from more than 150 countries and were published in 2665 journals by 63747 authors from 24899 organizations. There is an uneven distribution of countries, organizations, and authors in T1D research, wherein 88.37%, 45.15%, and 20.66% of the global literature was contributed by the top 12 countries and top 30 organizations and authors each. The most productive countries were the USA and UK, with a global share of 30% and 11.1% respectively. The most impactful countries were Finland and the UK regarding CPP & Relative Citation Index (RCI). The Barbara Davis Center for Childhood Diabetes, USA, and the University of Colorado Anschutz Medical Campus, USA, were the most productive organizations, with 735 and 679 publications. Jaeb Center for Health Research, USA (77.03 and 2.64) and Harvard Medical School, USA (67.42 and 2.31) were the most impactful organizations regarding CPP & RCI. Pediatric Diabetes (n=1447) and Diabetes Care (n=1191) were the most productive journals, with 1447 and 1191 papers. Diabetes and Diabetes Care registered the highest CPP (81.54 and 73.88 CPP). The most significant and frequently appearing keywords were “diabetes mellitus, type 1”) (92441), “insulin dependent diabetes mellitus” (95750), “metabolism” (24911), “genetics” (11229), “autoantibodies” (8942), “c peptide” (9931) and “pancreas islet beta cell” (7191). Only 5.54% (1134) of the global publications (considered highly-cited papers) received 100 to 4654 citations since their publications and registered a total of 220.28 CPP. Conclusion. This bibliometric study indicated that most of the contributions came from developed countries and only a meager contribution from developing countries, especially South Asia, despite a significant disease burden. This analysis provides a comprehensive overview of the present status of T1D research. It enables a better understanding of T1D research over the years. It should give the researchers structured information and a comprehensive analysis to help identify gaps in the research and the hot spots in this area of research.